Shadow of the New Deal : the victory of public broadcasting - Shepperd, Josh, 1977- (History of communication., 2023)
"Despite uncertain beginnings, public broadcasting emerged as a noncommercial media industry that transformed American culture. Josh Shepperd looks at the people, institutions, and influences behind the National Association of Educational Broadcasters (NAEB) and its drive to create what became the Public Broadcasting Service and National Public Radio. Founded in 1934, the NAEB began as a disorganized coalition of undersupported university broadcasters. Shepperd traces the setbacks, small victories, and trial and error experiments that took place as thousands of advocates built a media campaign premised on the belief that technology could ease social inequality through equal access to education and information. The bottom-up, decentralized network they created implemented a different economy of scale and a vision of a mass media divorced from commercial concerns. At the same time, they transformed advice, criticism, and methods adopted from other sectors into an infrastructure that supported public broadcasting in the 1960s and beyond"--